A COLLECTION OF NATIONAL AND MODERN CLOTHES IN THE ETHNIC DIRECTION OF SURKHANDARYA PRET-O-PORTE DE LUX - Xatamova Aziza Ochildiyevna (Web of Journals Publishing, 2025)
In this article the combination of elements of traditional dress of the Surkhandarya region with modern fashion trends is studied within the framework of the Pret-a-Porter de Lux concept. The study analyzes the constructive transformation of national clothes, their adaptation to modern fashion, while preserving their cultural identity. The choice of materials, decorative elements, and the influence of ergonomic design on clothing aesthetics and functionality are discussed. The research results contribute to the development of national fashion, the combination of historical heritage and innovative design approaches, as well as the international recognition of the rich textile culture of Uzbekistan.
Keywords: National dress of Surkhandarya, ethno fashion, modern ethnostyle, Pret-a-porte De Lux, Uzbek design, combination of national and modern, Surkhandarya patterns, ethno collection, national fashion direction, Uzbek haute couture, traditional fabrics of Surkhandarya, design of national dresses, handmade decorations, modern ethno design, Uzbek fashion 2025, collection of dresses, designer collection, cultural heritage fashion.